Inhibition of p38 mitogen-activated protein kinases may attenuate scar proliferation after cleft lip surgery in rabbits via Smads signaling pathway - Qian Ding; Jin Yue; Ling-fa Xue; Yao-xiang Xu; Wen-lin Xiao (European Journal of Medical Research, 2022)
Abstract Background Cleft lip repair surgery always results in visible scarring. It has been proved that scar formation can be reduced by inhibiting the p38 mitogen-activated protein kinases (p38MAPKs) signaling pathway. However, the interaction between p38MAPK and Smads in scar formation is still controversial. Methods This study was designed to investigate whether inhibition of p38MAPK reduces postoperative scar formation of cleft lips on rabbits via the Smads signaling pathway. Scar models in rabbits after cleft lip surgery were created and their fibroblasts were extracted. Then the expression of p38MAPK was disturbed by adenovirus in vitro and Vivo. The scar thickness was measured and scar tissues were excised for Sirius red staining and immunohistochemistry to detect the expression of type I collagen (col I), type III collagen (col III), and α-smooth muscle actin (α-SMA). The underlying mechanisms of p38MAPK knockdown on the extracellular matrix and Smad signaling pathway were invested in vitro using the EdU assay, Western blot, RT PCR, and immunofluorescence. Results p38MAPK knockdown suppresses the expression of p-smad3 and p-smad2 in fibroblasts, modulating the expression of its target genes, such as α-SMA, col I, and col III. When Ad-P38MAPK-1 was injected into lip scar, it reduced the expression of scar-related genes and scar thickness when compared to the negative control groups. Conclusions In rabbits, inhibiting p38MAPK expression prevents scar proliferation through inhibiting the Smad signaling pathway after cleft lip surgery.